Pengaruh Media Chromebook terhadap Motivasi Belajar Peserta Didik Kelas V Materi Bumi Berubah di SDN Bendosari - Putra, Prima Rizkya; Jadmiko, Rahmad Setyo (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study was motivated by the low motivation of students in learning IPAS, especially in the material of Earth Changes in class V SDN 03 Bendosari. This condition is caused by the dominance of the lecture method and the lack of use of interactive learning media, making students less interested and tend to be passive in participating in the learning process. One of the solutions offered to overcome these problems is to utilize technology-based learning media, namely Chromebooks. The purpose of this study was to determine the effect of using Chromebook media on students' learning motivation. This study used a quantitative approach with a One-Group Pretest-Posttest Design. The research subjects consisted of 20 fifth grade students of SDN 03 Bendosari who were selected through saturated sampling technique. The research instrument is a learning motivation questionnaire which includes three main aspects, namely attention, confidence, and satisfaction, with a total of 20 statement items. Before use, the instrument was tested for validity and reliability with the help of the Jamovi 2.3.28 application. The validity test results show that the KMO value is 0.830 and the Bartlett's Test is significant (p < 0.001), indicating that the instrument is suitable for use. The reliability test shows the Cronbach's Alpha value of 0.939 which is included in the very high category. The results of the pretest and posttest data normality test using the Shapiro-Wilk test show a value of p = 0.985, which means that the data is normally distributed. Hypothesis testing was carried out with Paired Sample t-Test and obtained a significance value of 0.001 <0.05, which indicates that there is a significant difference between pretest and posttest scores. The average student learning motivation score increased from 65.9 in the pretest to 86.5 in the posttest. This shows that the use of Chromebook media in IPAS learning can significantly increase students' learning motivation. Thus, Chromebook media can be used as an effective alternative in creating more interesting, interactive, and meaningful learning for elementary school students.